2015
DOI: 10.4161/21645515.2014.994460
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of purified chick-embryo cell rabies vaccine under Zagreb 2-1-1 or 5-dose Essen regimen in Chinese children 6 to 17 years old and adults over 50 years: A randomized open-label study

Abstract: (2015) Immunogenicity and safety of purified chick-embryo cell rabies vaccine under Zagreb 2-1-1 or 5-dose Essen regimen in Chinese children 6 to 17 years old and adults over 50 years: A randomized open-label study , Human Vaccines & Immunotherapeutics, 11:2, 435-442, DOI: 10.4161/21645515.2014 The aim of this Phase IIIb, open-label, randomized study was to demonstrate the non-inferiority of immune responses and to assess the safety of a purified chick-embryo cell rabies vaccine (PCECV) in healthy Chinese ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Mild to moderate solicited local and systemic reactions, with pain being the most reported solicited local AE (38% and 40% of children following the Zagreb and Essen regimens, respectively) and fatigue as the most common systemic AE (15% and 13% of children after the Zagreb and Essen regimens respectively), were reported in a study on healthy children [25].…”
Section: Special Populationsmentioning
confidence: 89%
See 4 more Smart Citations
“…Mild to moderate solicited local and systemic reactions, with pain being the most reported solicited local AE (38% and 40% of children following the Zagreb and Essen regimens, respectively) and fatigue as the most common systemic AE (15% and 13% of children after the Zagreb and Essen regimens respectively), were reported in a study on healthy children [25].…”
Section: Special Populationsmentioning
confidence: 89%
“…A second study conducted among a subgroup of healthy children aged 1-5 years reported a GMT of 12.0 IU/mL on D14 and 13.0 IU/mL on D42 for the IM Zagreb regimen (2-1-1). For the Essen regimen (1-1-1-1-1) a GMT of 14.0 IU/mL was reported on D14 and 24.0 IU/mL on D42 [25]. For both regimens at Day 14, the seroconversion rate was 100% (95% CI: 97-100).…”
Section: Special Populationsmentioning
confidence: 99%
See 3 more Smart Citations